1997
DOI: 10.1007/s003810050155
|View full text |Cite
|
Sign up to set email alerts
|

Successful conservative management of Gorham disease of the skull base and cervical spine

Abstract: Gorham's disease, also called massive osteolysis or vanishing bone disease, is an enigmatic condition caused by endothelial proliferation occurring in bone and soft tissue. Death is frequent when there is spinal or visceral involvement. We present a case of spinal and skull base Gorham's disease that was reversed by radiation therapy administered while the spine was supported by a halo vest. The literature is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 21 publications
0
26
0
3
Order By: Relevance
“…The non-operative options include radiation therapy, 10,21,39,44,60,69,101,112,139,140 anti-osteoclastic medication (bisphosphonates), 109,146 and alpha-2b interferon. 109 The operative options include surgical resection, 10,29,63,69 reconstruction using a bone graft, 30,63 or a prosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-operative options include radiation therapy, 10,21,39,44,60,69,101,112,139,140 anti-osteoclastic medication (bisphosphonates), 109,146 and alpha-2b interferon. 109 The operative options include surgical resection, 10,29,63,69 reconstruction using a bone graft, 30,63 or a prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The medical treatment for Gorham's disease includes radiation therapy, 10,21,39,44,60,69,101,112,139,140 anti-osteoclastic medication (bisphosphonates), 109,146 and alpha-2b interferon. 109 The principal treatment modalities are surgery and radiation therapy.…”
Section: Treatmentmentioning
confidence: 99%
“…Only 28 cases, to our knowledge, have been reported in the English literature (Table 1) (Bickel and Broders 1947;Gorham and Stout 1955;Falkmer and Tilling 1956;Hambach et al 1958;Castleman and McNeely 1964;Ellis and Adams 1971;Thompson and Schurman 1974;Heyden et al 1977;Woodward et al 1981;Heffez et al 1983;Brown et al 1986;Bohlman et al 1986;Hejgaard and Olsen 1987;Joseph and Bartal 1987;Mitchell et al 1993;Drewry et al 1994;Halliday et al 1994;Stöve and Reichelt 1995;Aoki et al 1996;Livesley et al 1996;Chung et al 1997;Hagberg et al 1997;Mawk et al 1997;Benhalima et al 2001;Bode-Lesniewska et al 2002;Chong and Shell 2003;Ceroni et al 2004). Eighteen patients were males and 10 patients were females.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors stated that radiotherapy could not cease the progression of osteolysis (Cannon 1986;Stöve and Reichelt 1995;Livesley et al 1996;Chung et al 1997;Bode-Lesniewska et al 2002), and others reported favorable outcomes of radiotherapy alone, or in combination with a brace or halo traction, which not only prevented further progression of the disease but also lead to new bone formation in involved vertebrae (Heyden et al 1977;Heffez et al 1983;Mawk et al 1997). In the present case, radiotherapy was not chosen because its effect was controversial and there were too many vertebrae involved.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an additional report of recalcification after radiation therapy was published. 27 The major disadvantage to using radiation therapy for Gorham's disease is the possibility for acute and long-term side effects that vary by treatment site. Our patient developed radiation pneumonitis that required treatment with steroids.…”
Section: Discussionmentioning
confidence: 99%